Co-encapsulation of curcumin and β-carotene in Pickering emulsions stabilized by complex nanoparticles: Effects of microfluidization and thermal treatment. (January 2022) - Wei, Yang; Wang, Chao; Liu, Xin; Mackie, Alan; Zhang, Mengke; Dai, Lei; Liu, Jinfang; Mao, Like; Yuan, Fang; Gao, Yanxiang
Abstract: The objective of this study was to explore the influence of different particle concentrations (0.5%–3.0 %, w/v), microfluidization pressures (0–150 MPa) and heating temperatures (30–70 °C) on the physicochemical stability, microstructure, and in vitro digestion of β-carotene loaded Pickering emulsions stabilized by curcumin loaded complex nanoparticles. The optimum parameters for the fabrication of stable β-carotene loaded Pickering emulsions were 2.0 % (w/v) of particle concentration, 100 MPa of operating pressure and 60 °C of heating temperature. The co-encapsulation exhibited a synergistic effect on improving the photothermal stability of β-carotene and curcumin entrapped. During in vitro gastrointestinal digestion, the increased particle concentration (≥2.0 %, w/v) and heating temperature (≥50 °C) retarded the FFA release from the emulsions and reduced the bioaccessibility of curcumin and β-carotene through droplet flocculation. However, the lower pressure (≤100 MPa) promoted lipolysis and enhanced the bioaccessibility of nutraceuticals. The Pickering emulsion was designed for the co-delivery of curcumin and β-carotene via microfluidization and thermal treatment, which showed the great potential to be applied in the industrial production of functional foods and dietary supplements. Graphical abstract: Image 1 Highlights: Co-encapsulation improved the chemical stability of β-carotene and curcumin synergistically. The stability of Pickering emulsions was enhanced under different environmental stresses. The elevated particle concentration and heating temperature of Pickering emulsions retarded the FFA release. Microfluidization promoted the lipolysis and increased the bioaccessibility of nutraceuticals.